Residues of organochlorine pesticides in water sources of Istanbul - (:unkn) unknown (KLUWER ACADEMIC PUBL, 1999)
The concentrations of 9 chlorinated pesticides in the water sources and tap waters of Istanbul, Turkey, were determined by gas chromatographic methods following the enrichment through adsorption and elution techniques. The observed organochlorine pesticides were alpha- and gamma-HCH and aldrin which had been banned from use. The contents of alpha- and gamma-HCH in raw waters were in the range of 0.34-1.7 ppb and not detected-0.077 ppb, respectively. Aldrin was observed at the concentration of 0.03 ppb in some samples. The residue levels of organochlorine pesticides in drinking water supplies of Istanbul were found significantly under the maximum permissible levels of standards. The effectiveness of potable water treatment processes and the importance of maintenance and back-washing of sand filters in pesticide removal were observed. Improper and delayed back-washings of filters caused an increase in the pesticide residues in the distributed water. Ln older water distribution lines, higher concentrations of some organochlorines were also observed.
Keywords: drinking water; gas chromatography; lindane; organochlorine pesticide; residue analysis; SOLID-PHASE EXTRACTION; HEXACHLOROCYCLOHEXANE ISOMERS; POLYCHLORINATED-BIPHENYLS; CHLORINATED HYDROCARBONS; HYDROPHOBIC POLLUTANTS; GAS-CHROMATOGRAPHY; NATURAL SEDIMENTS; SOIL SUSPENSIONS; PERSISTENCE; SORPTION